Characterization of Fibroblast Secretome: Extracelular Vesicles (EVs) Particle Count, Molecular Size and Total Protein Levels - Riliani, Marisa; Kusuma, Indra; Sandra, Yurika; Zakiyah, Zakiyah; Ramansyah, Aditya (Faculty of Medicine Universitas Sebelas Maret, 2025)
Introduction: The secretome of human dermal fibroblasts consists of diverse bioactive molecules including proteins and extracellular vesicles (EVs), playing a key role in skin regeneration and homeostasis. Molecular weight-based fractionation provides insights into the functional heterogeneity of the conditioned medium (CM). This study aimed to characterize size-fractionated CM from fibroblasts to reveal its molecular properties and potential bioactivity.Methods: A descriptive laboratory study was conducted using conditioned medium from passage 5 human dermal fibroblasts cultured in serum-free conditions. Tangential flow filtration (TFF) was applied to fractionate the CM into low (LMW), medium (MMW), and high molecular weight (HMW) components. Nanoparticle tracking analysis (NTA) quantified EV particle concentration and size, while total protein content was assessed by BCA assay. Experiments were performed in triplicate (n=3).Results: Particle concentrations increased with molecular weight, with HMW fractions showing the highest counts but slightly smaller average particle sizes compared to LMW and MMW fractions. Total protein concentration also rose with molecular weight, peaking in HMW fractions, indicating enrichment of larger protein complexes and vesicles. Fractionation maintained consistent particle size distribution across fractions, supporting effective separation.Conclusion: Fibroblast secretome exhibits heterogeneous EV and protein populations distinguishable by molecular weight fractionation. The enriched higher molecular weight fractions contain more EVs and proteins, suggesting distinct biological roles. Combining TFF with further purification steps may enhance separation purity, facilitating therapeutic applications of secretome components.